The Interplay Between Reproductive Tract Microbiota and Immunological System in Human Reproduction - Al-Nasiry, Salwan; Ambrosino, Elena; Schlaepfer, Melissa; Morré, Servaas A.; Wieten, Lotte; Voncken, Jan Willem; Spinelli, Marialuigia; Mueller, Martin; Kramer, Boris W. (Frontiers in Immunology, 2020)
In the last decade, the microbiota, i.e., combined populations of microorganisms living inside and on the surface of the human body, has increasingly attracted attention of researchers in the medical field. Indeed, since the completion of the Human Microbiome Project, insight and interest in the role of microbiota in health and disease, also through study of its combined genomes, the microbiome, has been steadily expanding. One less explored field of microbiome research has been the female reproductive tract. Research mainly from the past decade suggests that microbial communities residing in the reproductive tract represent a large proportion of the female microbial network and appear to be involved in reproductive failure and pregnancy complications. Microbiome research is facing technological and methodological challenges, as detection techniques and analysis methods are far from being standardized. A further hurdle is understanding the complex host-microbiota interaction and the confounding effect of a multitude of constitutional and environmental factors. A key regulator of this interaction is the maternal immune system that, during the peri-conceptional stage and even more so during pregnancy, undergoes considerable modulation. This review aims to summarize the current literature on reproductive tract microbiota describing the composition of microbiota in different anatomical locations (vagina, cervix, endometrium, and placenta). We also discuss putative mechanisms of interaction between such microbial communities and various aspects of the immune system, with a focus on the characteristic immunological changes during normal pregnancy. Furthermore, we discuss how abnormal microbiota composition, “dysbiosis,” is linked to a spectrum of clinical disorders related to the female reproductive system and how the maternal immune system is involved. Finally, based on the data presented in this review, the future perspectives in diagnostic approaches, research directions and therapeutic opportunities are explored.